Defending probation: Beyond privatisation and security. (April 2014) - Fitzgibbon, Wendy; Lea, John
The current debate about the privatisation of probation in the UK has tended to set up a false dichotomy between state and private that diverts attention from the fact that privatisation as part of a 'rehabilitation revolution' intends, in fact, to continue the domination of the risk management approach. What is emerging is a public–private combination of increasingly centralised public sector probation and the private 'security-industrial complex' of global security corporations. An important consequence of this process is the annihilation of both residual elements of voluntary sector and community work within probation itself and of the smaller private charities and third sector organisations that have long collaborated with probation in traditional desistance work. This complex dynamic is a reflection of some of the key internal inconsistencies of neoliberalism as a political strategy.